Association between the Time of Length since Smoking Cessation and Insulin Resistance in Asymptomatic Korean Male Ex-Smokers. (19th June 2017) - Kim, Ko-Woon; Kang, Sung-Goo; Song, Sang-Wook; Kim, Na-Rae; Rho, Jun-Seung; Lee, Yun-Ah
Abstract : Aim. Smoking is a major risk factor for diabetes mellitus, mainly due to decreased insulin secretion and increased insulin resistance. However, there has been little research on the effects of smoking cessation period on changes in insulin resistance. In this study, we investigated the relationships between the length of time since smoking cessation period and insulin resistance in asymptomatic Korean male ex-smokers. Methods. A total of 851 male adults were included in this study. We considered several factors that can affect insulin resistance, and through multiple linear regression analysis, we assessed the effect the length of time since smoking cessation on insulin resistance in ex-smokers. Insulin resistance was represented as the insulin resistance index estimated by homeostasis model assessment. Results . HOMA-IR values showed a statistically significant negative correlation with the length of time since smoking cessation (p = 0.009 ) in ex-smokers. After performing multiple linear regression analysis using factors that could potentially influence insulin resistance, we found that waist circumference (p = 0.026 ) and the length of time since smoking cessation (p = 0.039 ) were independent predictors of HOMA-IR in asymptomatic male ex-smokers. Conclusion . The longer the smoking cessation period, the more the insulin resistance tended to decrease in asymptomatic Korean male ex-smokers.